Mechanical Calculation of Flexible Wires Loaded with Concentrated Loads - Y. V. Bladyko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Calculating of wires sag and tension under various modes is the task of mechanical calculation. The article derived formulas for the curve of the wire sag under the action of one or several concentrated forces and with various tensioning insulators strings in the span. Formulas for estimating the distance to the maximum sag have been obtained. Based on the length of the system of “first tension insulators string – conductors – second tension insulators string” that depends on the supporting beam reactions and beam lateral forces in the corresponding sections, the system load factor was determined taking into account structural elements for different climatic loads. The formulas to calculate the load factor for solving the equation of state in the case of different insulators strings in span loaded with one or several concentrated forces have been obtained. The resulting expressions can also be applied in case of horizontal wind loads; in this case the equation of state should take this component into account when calculating the resulting reduced load on the wire in an inclined plane. The reliability of the formulas was proved by the coincidence of the results for the particular case of the arrangement of the insulators strings. An algorithm for calculating sag under the combined action of vertical and horizontal loads, as well as in the case of the location of wire suspension points at different heights, is given. A formula has been proposed for estimating the sag increase factor due to the presence of concentrated forces uniformly distributed along the span and various insulator strings in the span. The dependence of the coefficient of increase of the sag on the distance to the concentrated force in the presence of one and two forces in the span is drawn.